The letter of James - McKnight, Scot. (Grand Rapids, Mich. : W.B. Eerdmans Pub. Co., 2011)
Scot McKnight's commentary expounds James both in its own context and in the context of ancient Judaism, the Greco-Roman world, and the emerging Christian faith. --from publisher description.
James in the story -- James: who wrote the letter? -- What are the central themes of James? -- What is the structure of James? -- Commentary. Salutation (1:1) -- The Christian and trials (1:2-18) -- General exhortations (1:19-27) -- The Christian and partiality (2:1-13) -- The Christian and works (2:14-26) -- General exhortations for teachers (3:1-4:12) -- The Messianic community and the wealthy (4:13-5:11) -- Concluding exhortations (5:12-20).
Includes bibliographical references (pages xix-xxx) and indexes.
Print version.
Master record variable field(s) change: 050
Keywords: Bible. -- Commentaries; Bible; RELIGION -- Biblical Studies -- New Testament; RELIGION -- Biblical Studies -- Paul's Letters; Electronic books; Commentaries